ESBL-producing Escherichia coli: a molecular study on bacterial relatedness and resistance genes in isolates from the period 2006-2014 - Hildur Byström Guðjónsdóttir 1983- (2015)
Introduction. The prevalence of extended-spectrum β-lactamases (ESBL) in members of the Enterobacteriaceae family increases steadily and causes difficulties in the treatment of infectious diseases. Escherichia coli is the commonest pathogen in the family and the most prevalent ESBL in this species is the CTX-M-15 derivative. The blaCTX-M-15 gene has spread rapidly around the world, in part via the transmissive E. coli ST131. The prevalence of ESBL-producing E. coli in Iceland is low but rising. Although nosocomial outbreaks due to E. coli are uncommon, such an outbreak occurred recently at Landspítali – The University Hospital of Iceland. Information about bla genotypes in E. coli is incomplete in Iceland, and no studies have been published on phylogenetic and multilocus sequence typing (MLST) of E. coli in the country. Methods. The objective of the study was to perform molecular typing with regard to clonality, phylogeny, bla genes and MLST of ESBL-producing E. coli from community acquired infections during the years 2006-2012 and from an outbreak that occurred in the neonatal intensive care unit (NICU) at Landspítali in early 2014. All community isolates selected for this study were examined with pulsed-field gel electrophoresis (PFGE) of macroresticted DNA, and typing of phylogeny groups and bla genes with PCR. All NICU isolates were analyzed with PFGE, and a selected subgroup was subjected to typing of phylogeny groups and bla genes. Six community isolates and one NICU isolate were analyzed with MLST. Results. A total of 138 community isolates, from as many patients, were analyzed. PFGE analysis revealed 126 clones and 36% and 37% of all isolates belonged to phylogroups B2 and D, respectively. blaCTX-M, blaSHV and blaTEM were detected in 112, 14 and 73 isolates, respectively. Sequencing of blaCTX-M, genes was done for 42 CTX-M positive isolates; 21 produced CTX-M-15. MLST revealed ST43 (corresponds to ST131) for the six community isolates analyzed. A total of 37 NICU isolates (from 25 infants, three family ...